2022
DOI: 10.3389/fendo.2022.942271
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Affection of Pre-Pregnancy Overweight or Obesity, Excessive Gestational Weight Gain and Glucose Tolerance Test Characteristics on Adverse Pregnancy Outcomes Among Women With Gestational Diabetes Mellitus

Abstract: PurposeTo examine the combined effect of pre-pregnancy overweight or obesity, excessive gestational weight gain, and glucose tolerance status on the incidence of adverse pregnancy outcomes among women with gestational diabetes mellitus.MethodsA observational study including 5529 gestational diabetes mellitus patients was performed. Logistic regression were used to assess the independent and multiplicative interactions of overweight or obese, excessive gestational weight gain, abnormal items of oral glucose tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
1
5
0
1
Order By: Relevance
“…In GDM women, excessive gestational weight gain may further increase the risk of adverse maternal and perinatal outcomes, which was consistent with the present study [38][39][40]. Excessive gestational weight gain could lead to increased insulin resistance and abnormal distribution of adipose tissue, which further contribute to impaired maternal metabolism and unhealthy intrauterine environment [41].…”
Section: Discussionsupporting
confidence: 89%
“…In GDM women, excessive gestational weight gain may further increase the risk of adverse maternal and perinatal outcomes, which was consistent with the present study [38][39][40]. Excessive gestational weight gain could lead to increased insulin resistance and abnormal distribution of adipose tissue, which further contribute to impaired maternal metabolism and unhealthy intrauterine environment [41].…”
Section: Discussionsupporting
confidence: 89%
“…This could be explained by the fact that GDM is not the only factor resulting in fetal macrosomia; other known risk factors are multiparity, older age, previous LGA and a male newborn. In addition, pregnancy weight gain and pre-pregnancy BMI have been shown in previous studies to be related to GDM but also to isolated LGA newborns [ 30 , 31 , 32 ]. In our cohort, the most noticeable difference among high-risk women with no OGTT and a normal OGTT result was extensive weight gain and a more frequent need for operative delivery due to LGA neonate among the normal OGTT group.…”
Section: Discussionmentioning
confidence: 99%
“…Data on 2630 women indicated that EGWG in early pregnancy more severely affects maternal health, while later weight gain impacts a neonate, increasing the risk of a cesarean section, and LGA, regardless of fetal sex and macrosomia, especially in male fetuses [ 92 ]. Another research work revealed that a higher prevalence of macrosomia and LGA in neonates born to mothers with GDM who gained excess weight during pregnancy is additionally increased by concurrent overweight or obesity as well as abnormal results from an oral glucose tolerance test (OGTT) [ 93 ].…”
Section: Fetal Programming For Metabolic Diseases In Children Born To...mentioning
confidence: 99%